Sistema de recomendação de tags aplicado na catalogação de recursos de aprendizagem - Amaral, Anderson Roque do (2014)
Aspects of social tagging have been studied in the last years aiming at addressing concepts, applicability and techniques related to the generation and management of tags as key elements for the resource research and classification. Social tagging has been recognized as an important alternative for the description of resources available on the Web. Concerning on the rapid growth of resources and their information on the Web, it has become increasingly difficult to find and organize such massive data by traditional methods as based on directories classification. The process of social tagging has been investigated to improve the cataloging of resources, being recommendation algorithms of tags, visualization techniques and automatic generation of tags, among others have been explored for this purpose. Within the e-learning context, the social tagging may assist on building of metadata of learning objects. Thus, all the advantages linked to this model of resources organization, has emerged as solutions for e-learning systems. The main contribuition of a teaching-learning environment is the creation, storing and maintenance of the catalog of learning resources that can be checked and updated continuously. This work proposes a tags recommendation system, improving the process of cataloguing of learning resources on the web. Three experiments were carried out with technician students of a informatics course to validate the proposal: the first one examined the social tagging activity without using the tag recommendation system; the second one was conducted to evaluate the tagging activity, but including the tags recommendation system; and the third one verified the students navigation from the tagged resources created from the first and the second experiment, in order to check that the support of the recommendation was effective in the descriptor vocabulary of the resource.